2017
DOI: 10.1007/978-3-319-58689-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Assessments of Adult Literacy

Abstract: Educational Testing Service's (ETS's) work in large-scale adult literacy assessments has been an ongoing and evolving effort, beginning in 1984 with the Young Adult Literacy Survey in the United States. This work has been designed to meet policy needs, both in the United States and internationally, based on the growing awareness of literacy as human capital. The impact of these assessments has grown as policy makers and other stakeholders have increasingly come to understand the critical role that foundational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“… a By design, the sample was half younger (20–44) vs older (45–65), half male vs female, and half normal weight (18.5–24.9) vs overweight/obese (25.0–35.0).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a By design, the sample was half younger (20–44) vs older (45–65), half male vs female, and half normal weight (18.5–24.9) vs overweight/obese (25.0–35.0).…”
Section: Resultsmentioning
confidence: 99%
“… a By design, the sample was half younger (20–44) vs older (45–65), half male vs female, and half normal weight (18.5–24.9) vs overweight/obese (25.0–35.0). b Objectively measured BMI. c Based on International Standard Classification of Occupations (42). d Based on International Physical Activity Questionnaire, Short Form (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both the workplace and everyday life, it has become increasingly important that adults are able to navigate, critically analyze, and problem solve in data-intensive, complex digital environments-and PIAAC has made it possible to measure such skills. In addition, PIAAC has introduced methodological innovations such as multistage adaptive testing and flexible routing for the background questionnaire that have improved the design and delivery of the survey and laid the foundation for future assessments (Kirsch et al 2017). …”
Section: Assessing Adult Populationsmentioning
confidence: 99%
“…In the modern, and increasingly digital era of healthcare, text readability plays a significant role in dictating the extent of a patient's participation within their own care. As the average American adult reads at an eighth-grade level, 3 the National Institutes of Health (NIH) and American Medical Association (AMA) have recommended that all patient education materials be written at or below a sixth-grade reading level to increase both health literacy and health access for the average patient 4 . A plethora of research has shown that providers significantly overestimate the level of patient understanding during the informed consent process 5–7 and a wide array of patient reading materials across all sectors of medicine have been demonstrated to be far too complex for most patients to understand 8–15 .…”
mentioning
confidence: 99%